Enterprise Risk Management (ERM) dan Risiko Gagal Bayar: Analisis Empiris pada BUMN Non-Keuangan di Indonesia - Hidayah Widyaningrum (Economic Reviews Journal, 2025)
This study investigates the impact of Enterprise Risk Management (ERM) on default risk in Indonesian non-financial state-owned enterprises (SOE’s). Using 231 firm-year observations from 48 SOEs over the 2019–2023 period, the study employs the System Generalized Method of Moments (System GMM) to address potential endogeneity and dynamic panel bias. The findings show that ERM has a negative and marginally significant effect on default risk, indicating its potential role in improving financial resilience. Additionally, profitability, liquidity, and leverage significantly reduce default risk, whereas corporate governance, firm size, and economic growth exhibit no significant influence. These results underscore the importance of strengthening ERM implementation and integrating it more effectively within the strategic management of SOE’s. The study contributes to the literature by providing empirical evidence on ERM’s role in mitigating default risk, particularly in state-owned enterprises operating in emerging markets. The findings also offer policy insights for enhancing ERM frameworks and governance practices in financially vulnerable public-sector firms.